(untitled) (International journal of artificial intelligence, 2025)
This article explores the growing significance of the Korean language in contemporary global culture. It examines how the rise of Korean popular culture, including K-pop, K-dramas, and Korean cinema, has propelled the language onto the world stage, fostering cross-cultural communication and influencing language learning trends worldwide. The paper also discusses the socio-economic and technological factors contributing to the Korean language’s international presence and considers its future role in global intercultural exchange.